THE ANTECEDENTS OF INDEPENDENCE AND WORK EXPERIENCE ON AUDIT QUALITY - Paramananda N. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
The profession of an auditor has been in the spotlight since the emergence of many audit cases involving public accountants which raised public doubts about audit quality. High quality auditing has always been the goals of every Public Accounting Firm. Audit quality is an audit characteristic that fulfills the requirements of auditing standards and quality control standards that represents audit practices and become the measure of quality in duties implementation to fulfill professional responsibilities. This study intent to explain empirically the effect of independence and work experience on audit quality in Bali public accountant Firm. The sampling technique used in this study is a purposive sampling technique. The samples in this study are all auditors who work at Public Accounting Firms (KAP) in Bali who have at least 1 year of experience carrying out audits. The analysis technique used in this research is Moderated Regression Analysis. This research was conducted at a Public Accounting Firm in Bali registered with the Indonesian Institute of Public Accountants (IAPI). The results of hypothesis testing show that independence and work experience collectively have a positive impact on audit quality.